Productive performance of broilers supplemented with tylosin phosphate or enramycin as growth promoters - Espinoza C., Sandra (2019)
The productive performance of broilers supplemented with tylosin phosphate and enramycin as growth promoters up to 42 days of age was evaluated. Four hundred male broilers were distributed into 4 treatments of 100 birds with 5 repetitions each. The treatments were: T1, control; diet without antibiotic; T2, diet with 8% enramycin in a dose of 10 ppm; T3, diet with enramycin 8% in a dose of 5 ppm; T4, diet with tylosin phosphate 25% in a dose of 55 ppm. The treated groups presented a higher body weight and better feed conversion index and European productive efficiency index than the control group; however, there were no differences in body weight gain, feed intake and mortality.